Social Transformation Through the Internalization of Islamic Educational Values in the Kampung Al-Qur’an Community - Martina Ayu Wulandari; Agus Maimun; Akhmad Nurul Kawakip (Fitrah: Journal of Islamic Education, 2026)
Islamic education faces challenges in contextualizing Islamic values amid social change and the increasingly complex currents of globalization. Islamic education is often viewed as overly theoretical and insufficiently equipped to address moral and social issues in society. This study aims to analyze the internalization of Islamic educational values and its implications for social transformation in Kampung Al-Qur’an, Mandailing Natal, Indonesia. The study employs a qualitative approach using the case study method within an interpretive paradigm. Data were collected through observation, in-depth interviews, and documentation involving religious leaders, community members, parents, and youth. The findings reveal that the internalization of values occurs through religious conditioning, the strengthening of social control, the exemplary role of community leaders, and the collective involvement of families and the community. These practices successfully fostered spiritual discipline, social solidarity, and moral resilience within the community despite being situated in an environment vulnerable to negative influences. This study affirms that community-based Islamic education holds great potential as a model for sustainable and contextual social transformation.